2020
DOI: 10.1007/s10067-020-05312-z
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in delivering rheumatology care during COVID-19 pandemic

Abstract: COVID-19 has significantly affected healthcare systems around the world. To prepare for this unprecedented emergency, elective patient care was put on hold across the National Health Service (NHS). Rheumatology service had to be reorganised with a cancellation of elective clinics and clinical reconfiguration to continue to deliver care to patients, support frontline, and prevent viral transmission. The rheumatology community's responsibility of providing a continuity of care for patients had to be balanced wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 12 publications
1
29
1
2
Order By: Relevance
“…The risk of infections was thought to be slightly raised when patients with chronic inflammatory arthritis are treated with biologic anti-rheumatic drugs, particularly in elderly patients with co-morbidities [ 17 ]. The rationale to continue biologic drugs is mainly based on expert opinion and their clinical experience with the notion that the continuation of immunosuppressive drugs would minimise the disease flares and subsequent hospital admissions during the pandemic [ 5 , 18 ]. Although we did not specifically ask whether clinicians continued other forms of biologics, over 60% of clinicians favoured switching IV to SC biologics which is in line with NICE recommendation [ 4 ]; therefore, we can assume that most clinicians continued SC or oral forms of biologics for their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of infections was thought to be slightly raised when patients with chronic inflammatory arthritis are treated with biologic anti-rheumatic drugs, particularly in elderly patients with co-morbidities [ 17 ]. The rationale to continue biologic drugs is mainly based on expert opinion and their clinical experience with the notion that the continuation of immunosuppressive drugs would minimise the disease flares and subsequent hospital admissions during the pandemic [ 5 , 18 ]. Although we did not specifically ask whether clinicians continued other forms of biologics, over 60% of clinicians favoured switching IV to SC biologics which is in line with NICE recommendation [ 4 ]; therefore, we can assume that most clinicians continued SC or oral forms of biologics for their patients.…”
Section: Discussionmentioning
confidence: 99%
“…To deliver safe and effective care to patients, a balance must be achieved between protecting patients and staff from viral transmission whilst providing a continuity of care. Rheumatology services across the UK had to be reconfigured and reorganised to rise to these challenges [ 5 ]. This survey evaluates the impact of the pandemic on rheumatology service provision as perceived by rheumatologists in the UK and various strategies adopted to provide effective clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…In rheumatology, various reports have broadly documented the use of telemedicine, highlighting both its advantages and potential drawbacks [ 1 ]. The British Society for Rheumatology has issued guidance for patients on immunosuppressants during the present period, which includes the advice to remain at home as much as possible [ 13 ], and it has been reported that many rheumatology clinics in the UK have temporarily converted large proportions of outpatient activity to telephone clinics [ 14 , 15 ]. Notwithstanding the obvious advantages of telemedicine, which are amplified during the current pandemic, and the many reports of its use, in reality only very few studies have been published on the impact of telemedicine in care of patients in rheumatology clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Covid-19-pandemien har endret måten personer med revmatisk sykdom følges opp (4) og har synliggjort behovet for digitale alternativer som gir effektiv og trygg pasientoppfølging (5). Videokonsultasjoner kan bidra til bedre helsetjenestetilbud og vaere et akseptabelt alternativ til fysisk oppmøte for de som bor i avsidesliggende strøk (6)(7)(8).…”
Section: Fortolkningunclassified